Understanding Conflict Between Religious/Spiritual and Queer Identities: A Framework for Counselors. Issue 2 (1st October 2021) - Killian, Thomas; Levering, Kimery R.; Brottem, Lainey J.
Abstract : All individuals possess multiple intersecting identities, both contextually determined and at various stages of development. Contradictory or incompatible societal expectations attached to differing identities may cause internal conflict. Simultaneous navigation of queer and religious/spiritual identities may result in experiencing lack of affirmation and negative messaging, affecting successful negotiation and integration of these two identities, potentially affecting mental health. Awareness of this potential intersectional conflict is important for counselors treating these individuals. Here we present counselors with a framework for understanding intersecting identities by applying self‐categorization theory and exploring the continued influence effect.